PENGARUH ONLINE CUSTOMER REVIEW DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA E-COMMERCE LAZADA DI KOTA BANDUNG - Rostiawati, Iis (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2024)
Currently, the online marketplace in Indonesia is dominated by 5 e-commerce that have a balanced reputation, one of which is Lazada. At the beginning of 2024, the number of Lazada visitors experienced a greater decline than other e-commerce. The decline in visitor frequency and market share indicates that Lazada needs a business strategy to be able to increase purchasing decisions which in turn can affect consumer confidence. This study discusses the effect of online review and prices of purchasing decisions on Lazada marketplace users. This study uses quantitative methods and the data analysis technique are multiple linear regression with questionnaire research as the instruments. Respondents in this research are Lazada application users in Bandung and the number of samples determined is 96 samples. The results of this study indicate that the variables of customer online review and price have a positive and significant effect simultaneously on purchasing decisions, but partially customer online review has no effect on purchasing decisions. The results of the study can be a reference for Lazada to improve the quality of the product in order to get a rating and positive reviews from consumers to increase sales.